2011
DOI: 10.1073/pnas.1109208108
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic basis for the differential susceptibility of Gram-positive pathogens to fatty acid synthesis inhibitors

Abstract: Bacterial fatty acid synthesis (FASII) is an attractive target for treatment of Gram‐positive pathogens. The value of FASII inhibitors was recently questioned based on the ability of Streptococcus agalactiae to circumvent inhibition by utilizing exogenous fatty acids (FA) for phospholipid synthesis. This study compares the efficacy of FASII inhibitors against Staphylococcus aureus and Streptococcus pneumoniae grown in media containing FA. Exogenous FA overcame inhibition in S. pneumoniae, but not S. aureus. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
375
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(398 citation statements)
references
References 45 publications
22
375
1
Order By: Relevance
“…However, our experiments establish that Neisseria cannot circumvent FabI inhibition by scavenging fatty acids from the environment. In S. aureus, FabI inhibition blocks the uptake of fatty acids due to the depletion of cellular ACP as the initiation module of FASII continues to feed acyl-ACP into the elongation cycle and the enoyl-ACP intermediates accumulate at the inhibited step (35). AFN-1252 also inhibits the incorporation of extracellular fatty acids into Neisseria consistent with the blockade at the FabI step triggering the same imbalance in fatty acid metabolism in both organisms.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, our experiments establish that Neisseria cannot circumvent FabI inhibition by scavenging fatty acids from the environment. In S. aureus, FabI inhibition blocks the uptake of fatty acids due to the depletion of cellular ACP as the initiation module of FASII continues to feed acyl-ACP into the elongation cycle and the enoyl-ACP intermediates accumulate at the inhibited step (35). AFN-1252 also inhibits the incorporation of extracellular fatty acids into Neisseria consistent with the blockade at the FabI step triggering the same imbalance in fatty acid metabolism in both organisms.…”
Section: Discussionmentioning
confidence: 71%
“…Lipoic acid was provided because it is an essential cofactor for ketoacid dehydrogenases and is derived from octanoyl-ACP arising from FASII (52)(53)(54). S. aureus lacking FASII require exogenous lipoate in addition to fatty acids to support maximum growth (35,55). These experiments showed that exogenous fatty acids cannot bypass the inhibition of FabI by AFN-1252 in both N. gonorrhoeae and N. meningitidis.…”
Section: Exogenous Fatty Acids Cannot Overcome Growth Inhibition By Amentioning
confidence: 98%
See 1 more Smart Citation
“…In species related to Streptococcus agalactiae, extracellular FA can completely replace endogenously synthesized FA, rendering the FASII inhibitors ineffective growth inhibitors if sufficient FA are present (1,2). In contrast, FASII inhibitors exemplified by the enoyl-acyl carrier protein (ACP) reductase therapeutic AFN-1252 are effective against Staphylococcus aureus, even when extracellular FA are abundant (2,3). A major impediment to our understanding of this diversity is that the pathway and enzymes responsible for the incorporation of extracellular FA is not established in the Firmicutes.…”
mentioning
confidence: 99%
“…This physiologically process is not critical for many bacteria, as they can compensate the lack of synthesized fatty acids by uptake of exogenous molecules. However, suppression of fatty acid synthesis 8 becomes lethal for S. aureus because of a peculiarity of the regulation of fatty acid metabolism in this bacterium suppressing at the same time both the synthesis and incorporation of exogenous fatty acids [19]. In the latter paper it was explained why FabI inhibitors were much more toxic to S. aureus than to other micro-organisms.…”
Section: Demonstrated In Experiments Onmentioning
confidence: 98%